Exploring Feminism Through Critical Discourse: An Analysis of Adina Dwifatna's “Si Nuri” Using Sara Mills' Framework - Rahmani, Irfa Luthfia (Journal of English for Specific Purposes in Indonesia, 2025)
This research examines the representation of feminism in the short story "Si Nuri" written by Adina Dwifatna using Sara Mills' theory of critical discourse analysis feminism. The story revolves around the life and inner struggles of Ira, a wife to Martin. Women in the story are depicted as objects used to serve their husbands, manage household chores, and fulfill the role of motherhood. Hence, the researcher aims to explore the representation and the injustices experienced by the main female character in "Si Nuri." Furthermore, the researcher uses a descriptive qualitative method and documentation techniques to collect the data for this research. Meanwhile, to analyze the data the researcher uses content analysis techniques. The findings reveal that the story portrays women as confined to societal expectations and restricted in their freedom and autonomy. The gender stereotypes associated with the roles assigned to women perpetuate injustice, leading to the limitations felt by woman. Language and symbols employed in the story reinforce the social constructions that uphold gender inequality, with language reflecting power dynamics and social dominance centered around men.